DEVELOPMENT OF THE RENDANG INDUSTRIAL INNOVATION SYSTEM IN PAYAKUMBUH CITY - Imelfina Musthafa; Firwan Tan (Transpublika Publisher, 2023)
This research aims to examine efforts to develop an innovation system for the rendang industry in Payakumbuh City. The methodology used in this research is interviews with related parties regarding efforts to develop an innovation system for the rendang industry in Payakumbuh City. The results obtained are that there are various efforts to develop an innovation system for the rendang industry in Payakumbuh City, namely: the establishment of a rendang industrial center, rebranding of Payakumbuh City, the establishment of UPTD P3R, the establishment of the